Alergias e intolerâncias alimentares: comportamento e perfil dos consumidores - uma revisão bibliográfica - Ferrari, Beatriz Lisboa; Meira, Kelly Cristina; Soares, Maysa Pádua (Universidade Federal de São Carlos, 2022)
In recent years, with industrialization, the food sector has been transforming and accompanying changes in society. Such changes are related to consumer health, which has been developing some types of food intolerances and allergies. Food allergy is the abnormal reaction of the human immune system, through the ingestion of allergenic foods. Unlike allergies, food intolerance isn’t an exaggerated reaction to organisms not related to the immune system, but due to deficiencies and or lack of digestive enzymes produced by the body. Consumers with food intolerance or allergy showed a loyalty profile due to the difficulty and trust in new foods, however, many of them showed dissatisfaction with the commercialized ones, and are willing to spend more on higher quality products, allowing the insertion of new brands in the market. In addition, the female consumer profile stood out in the surveys, being responsible for the greater commercialization of foods intended for lactose intolerant and gluten allergy, and the child consumer profile had greater evidence in foods intended for casein allergy. That said, the present study aimed to analyze the most common types of allergies and intolerances, namely lactose intolerance, cow's milk protein allergy (CMPA) and gluten allergy (celiac disease), highlighting the needs of the consumer according to their consumption profile and therefore we analyze technologies applied to meet the demand for hypoallergenic foods.
Food allergies and intolerances: consumer profile - a bibliographic review
Keywords: Alergia alimentar; Intolerância alimentar; Leite; Caseína; Lactose; Glúten; Doença celíaca; Perfil do consumidor; Tecnologia; Food allergy; Food intolerance; Milk Casein; Lactose; Gluten; Celiac disease; Consumer profile; Technology; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS